The apothecary diaries. 2 - Hyūga, Natsu (Apothecary diaries ;, 2024)
"Maomao returns to imperial service, now as a personal servant to Jinshi! Other servants of the outer court eye her with jealousy. but that becomes the least of her concerns. A suspicious warehouse fire. An official with severe food poisoning. An intriguing last will that a deceased craftsman leaves behind. Though they seem separate, could a dark plot weave them all together? There's also the mysterious military man who keeps visiting Jinshi... And this odd, creepy man has an unsettling interest in Maomao"--